A Feature-Based Model for Nested Named-Entity Recognition at VLSP-2018 NER Evaluation Campaign - Pham, Minh Quang Nhat (Journal of Computer Science and Cybernetics, 2019)
In this report, we describe our participant named-entity recognition system at VLSP 2018 evaluation campaign. We formalized the task as a sequence labeling problem using BIO encoding scheme. We applied a feature-based model which combines word, word-shape features, Brown-cluster-based features, and word-embedding-based features. We compare several methods to deal with nested entities in the dataset. We showed that combining tags of entities at all levels for training a sequence labeling model (joint-tag model) improved the accuracy of nested named-entity recognition.